2019
DOI: 10.1002/cptc.201900203
|View full text |Cite
|
Sign up to set email alerts
|

The Right Light: De Novo Design of a Robust Modular Photochemical Reactor for Optimum Batch and Flow Chemistry

Abstract: European Union's Horizon 2020 program Marie Skłodowska-Curie (764920) for funding. We are grateful to the industrial affiliates of the Centre of Excellence for Biocatalysis (CoEBio3) for a studentship to T.M. Scheme 6. AaeUPO-catalyzed hydroxylation of 15 using Au-TiO 2 .Scheme 7. Aryl iodide and sulfinic acid salt cross-coupling model reaction used for reaction optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 39 publications
(46 reference statements)
0
65
0
1
Order By: Relevance
“…(intensity based on space). We have found that the angle of the LED lens affects this parameter 11 .…”
Section: Additional Considerations For Scalingmentioning
confidence: 88%
See 2 more Smart Citations
“…(intensity based on space). We have found that the angle of the LED lens affects this parameter 11 .…”
Section: Additional Considerations For Scalingmentioning
confidence: 88%
“…For literature reactions that we have reproduced, we have discovered that, although the air surrounding a reactor can be at ambient temperature, it is not uncommon for the internal reaction temperature to reach 60°C-80°C 11 . The specific type of reactor used for a reaction affects the internal reaction temperature 11 . Signifying the reactor configuration and any heat transfer elements used is the key.…”
Section: Stark-einstein Law or Photoequivalence Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it comes to meet the need of the pharmaceutical industry for characterized commercial photoreactors. [16] Experimental Section…”
Section: Discussionmentioning
confidence: 99%
“…4 A rising interest in photochemistry has been seen from the pharmaceutical industry. 5 Organic photoredox catalysts are growing in popularity due to the avoidance of expensive and toxic metals such as ruthenium and iridium. 6 Acridinium salts are among the most popular of these.…”
mentioning
confidence: 99%